THE EXPLOITATION OF INFORMATION GAP ACTIVITY IN TEACHING SPEAKING SKILLS FOR STUDENTS OF THE INTERNATIONAL STANDARD PROGRAM = SỬ DỤNG HOẠT ĐỘNG KHOẢNG TRỐNG THÔNG TIN TRONG VIỆC DẠY KĨ NĂNG NÓI CHO SINH VIÊN NHIỆM VỤ CHIẾN LƯỢC - Nguyễn, Hoàng Giang (ĐHQGHN - Đại học Ngoại Ngữ, 2021)
This study has been conducted with the aim to provide an insight into how teachers in the Faculty of English Language Teaching Education, ULIS employ information gap activities (IGA) in their teaching speaking to students of the International Standard Program. The research was carried out using multiple-case study design, with the two participants are the teachers who employ information gap activity most frequently in their teaching. It first aims at discovering the kinds of information gap activity and the techniques in facilitating the activity most commonly employed by the participants. More than that, the study attempted to uncover the reasons underlying teachers’ preferences as well as evaluating the effectiveness of each technique. Lastly, obstacles to the exploitation of IGA are also addressed. To fulfill these objectives, both qualitative and quantitative methods were employed, including the use of surveys of questionnaires, interviews and class observations. Results showed that both participants preferred the use of Exchanging personal information activity most due to its simplicity, flexibility and adaptability. In addition, among all the technique applied by the two teachers during their exploitation of IGA, forming groups randomly, giving instructions “step-to-step”, and monitoring the class discreetly proved to be more useful than other techniques. Besides, the study also reveals the challenges faced by teachers and students related to class layout, cooperation among students, and class noise. To make this research paper a valuable referencing resource for other teachers who want to employ IGA in their teaching, recommendations for an effective use of activities and techniques are also provided